THE GUISE OF U.S. NATIONAL REFERRAL AUTHORITY TO “OTHERING” REFUGEES AND ASYLUM SEEKERS: A TWAIL APPROACH - Alifa Salsabila (Universitas Gadjah Mada, 2020)
President Trump’s issuance of Executive Order 13769 titled “Protecting the Nation from Foreign Terrorist Entry into the United States” restricts and even bans access to refugees and asylum seekers from seeking international protection in and from the United States. It is done by creating narratives that refugees and asylum seekers are capable of committing “potential threats” under the umbrella of terrorism. This study aims to dismantle the paradoxes the Executive Order conveys. It focuses on the international refugee regime under the ambit of international law and a broader context of immigration debates—socially, economically, and culturally. This study uses theThird World Approach to International Law (TWAIL),making it possible for academic legal discussionto correspond in cultural context. The findings show that Trump’s Executive Order 13769 functions as the tool for the United States to “othering” refugees and asylum seekers as foreign terrorists in order to wage its national interests while ruling out humanity and the regime.